1974
DOI: 10.1364/ao.13.000808
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Holographic Read-Write Memory Using 3-D Storage

Abstract: A mockup of an experimental 3-D holographic read-write memory is described. The storage technique uses superimposed holographic pages in a thick photosensitive medium. Access to any page is obtained by reference beam rotation about each selected page. The experimental arrangement consists of a partially filled memory plane. The thick erasable storage medium used is iron-doped lithium niobate. The paper also includes experimental results on the deflector device, page composer, and readout systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…We can create an identical plane wave by using a 2D non-mechanical angle scanner in this plane A. One such example is two crossed AOD cells with cylindrical accessing lenses [ 7,8]. The Doppler shift added by these cells can be removed by an electrooptic modulator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We can create an identical plane wave by using a 2D non-mechanical angle scanner in this plane A. One such example is two crossed AOD cells with cylindrical accessing lenses [ 7,8]. The Doppler shift added by these cells can be removed by an electrooptic modulator.…”
Section: Discussionmentioning
confidence: 99%
“…The first involves mechanically moving the storage medium to access different spatial locations [ 10,111. The second method uses acoustooptic deflectors ( AODs) to perform both angle and spatial multiplexing [6][7][8][9]121, which leads to fast random access at the expense of a more complex optical system.…”
Section: C=nmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early 1970s, photorefractive media were investigated for use in holographic data storage devices because of the potentially high storage capacity [19]- [21]. Theoretical investigations indicated that a potential storage density of 10 b/cm could be achieved [22], with data transfer rates exceeding gigabits per second.…”
Section: Brief History and State Of The Artmentioning
confidence: 99%
“…This quantity allows two data channels in quadrature for each grating orientation, which generally requires coherent demodulation to separate the data channels. For one data channel in each grating direction, the total number of accessible data channels is given by [26] and [28] (19) Equation (19) indicates that a material with an index of refraction of 2.5, such as lithium niobate, has a channel density of 2 10 resolvable grating vectors. In a practical application, the number of degrees of freedom is reduced by a factor to 10 to 10 due the limited NA of a signal beam and limited angular excursion of the reference beam.…”
Section: Grating Vectors As Data Channelsmentioning
confidence: 99%